(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
Studies show that the dissemination of discriminatory views and stereotypes by commercial media do not go towards defending the rights of native peoples in Brazil. However, there are few studies on how native peoples use technologies to communicate and deal with such discrimination. This article looks to fill this gap by presenting the results of a study on the subject, aimed at producing scientific knowledge about the indigenous network known as Mídia India and their presence on Instagram. We achieved this by conducting a narrative analysis of 31 posts from 2019 in response to stereotypes and hegemonic degrading views. The results suggest that this network differs itself by holding constructive dialogues about stereotypes and questioning them in order to generate serious thought and deconstruct the stereotypes.